Association Between Cardiopulmonary Bypass–Induced Sirtuin-1 Suppression and Apoptosis - Amaç, Bişar; Göç, Ömer; Engin, Mesut; Yavuz, Senol (The European Research Journal, 2026)
Objectives: The aim of this study is to investigate, at the molecular level, the effect of cardiopulmonary bypass (CPB) on Sirtuin-1 levels, an epigenetic-metabolic regulatory protein, and the relationship between this change and Caspase-3, one of the key executor molecules of cellular apoptosis. Methods: Patients undergoing open heart surgery under CPB were included in the study. Sirtuin-1 and Caspase-3 levels were measured in venous blood samples taken from patients during the preoperative, intraoperative, and postoperative periods. The Wilcoxon Signed Ranks test was used to analyze differences between time points. Results: Sirtuin-1 levels decreased significantly during the intraoperative period compared to preoperative values (Z= -6.212, P